2000
DOI: 10.1023/a:1008393031299
|View full text |Cite
|
Sign up to set email alerts
|

Proposing phase I studies: Patients', relatives', nurses' and specialists' perceptions

Abstract: Informing patients on the option of receiving an investigational treatment within a phase I study is feasible and can be done in a way felt appropriate by patients and relatives, nursing and medical professionals. Providing information in an appropriate manner does not increase patients' anxiety and depression. Divergence between the aims and interests of the investigators and patients might explain the difference in the evaluation of physician, a problem which could perhaps be partially overcome by the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Research demonstrates that investigators expect greater benefits and higher toxicity than studies show [6,19,20], and observation is needed to ensure investigators are not communicating unsupported beliefs and expectations to patients. Trust in the investigator is an important factor in the decision-making process [9,22,24,25]; hence, investigators have a responsibility to be aware of their own agendas and communicate unbiased information.…”
Section: Resultsmentioning
confidence: 99%
“…Research demonstrates that investigators expect greater benefits and higher toxicity than studies show [6,19,20], and observation is needed to ensure investigators are not communicating unsupported beliefs and expectations to patients. Trust in the investigator is an important factor in the decision-making process [9,22,24,25]; hence, investigators have a responsibility to be aware of their own agendas and communicate unbiased information.…”
Section: Resultsmentioning
confidence: 99%
“…Unfamiliar terms such as randomization and placebo are particularly hard to understand [6][9], as are concepts related to risks [10], [11], benefits [12][14], and the freedom to withdraw from the study [15][18]. Additionally it has been shown that many trial participants are unaware that they are enrolled in research [18][20].…”
Section: Introductionmentioning
confidence: 99%
“…palliative care) but do not seriously consider them. When asked why they choose to participate, they say that this is the only way for them to maintain their hope of fighting their cancer, and that almost no adverse effect, including death, would dissuade them from enrolling [17]. Again, rather than having therapeutic misconceptions, the interviewed patients demonstrate that they are guided by therapeutic optimism [18,19], with only 3% reporting personally to be very or somewhat unlikely to benefit from participating in phase I studies.…”
Section: Role Of Optimism Bias With Regard To Participating In Phase mentioning
confidence: 99%